PENGARUH INSTAGRAM TERHADAP KETERLIBATAN ORANG MUDA KATOLIK DALAM HIDUP MENGGEREJA - Lestari, Indri; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2020)
This research aims to analyze the impact of Instagram on the involvement of young Catholics in parish activities, focusing on their understanding and engagement with social media. The study explores whether Instagram, as a web-based social media platform, affects the participation of young Catholics in church-related activities. A qualitative research method was employed, with data collected through surveys and interviews with young Catholics who follow the “OMK Kristus Raja” Instagram account. The research was conducted within the parish community of Kristus Raja, where the Instagram account has been actively providing updates since its inception in May 2017. The findings reveal that all respondents consider the “OMK Kristus Raja” Instagram account to be consistently updated, making it an essential source of information about youth activities. The majority of young Catholics follow the account to stay informed and engaged with parish events. Furthermore, the posts shared on the account provide new insights and encourage greater participation in church activities. The study concludes that Instagram has a positive impact on the involvement of young Catholics in parish life by enhancing their access to information and fostering a sense of community.